Hyperghrelinemia in Prader‐Willi syndrome begins in early infancy long before the onset of hyperphagia. (29th October 2014) - Kweh, Frederick A.; Miller, Jennifer L.; Sulsona, Carlos R.; Wasserfall, Clive; Atkinson, Mark; Shuster, Jonathan J.; Goldstone, Anthony P.; Driscoll, Daniel J.
<x xml:space="preserve">Abstract</x> Circulating total ghrelin levels are elevated in older children and adults with Prader‐Willi syndrome (PWS). However, the presence or absence of hyperghrelinemia in young children with PWS remains controversial. We hypothesized that a more robust way to analyze appetite‐regulating hormones in PWS would be by nutritional phases rather than age alone. Our objectives were to compare total serum ghrelin levels in children with PWS by nutritional phase as well as to compare total ghrelin levels in PWS (5 weeks to 21 years of age) to normal weight controls and individuals with early‐onset morbid obesity (EMO) without PWS. Fasting serum total ghrelin levels were measured in 60 subjects with PWS, 39 subjects with EMO of unknown etiology, and in 95 normal non‐obese sibling controls of PWS or EMO subjects (SibC) in this 12 year longitudinal study. Within PWS, total ghrelin levels were significantly (P < 0.001) higher in earlier nutritional phases: phase 1a (7, 906 ± 5, 887); 1b (5, 057 ± 2, 624); 2a (2, 905 ± 1, 521); 2b (2, 615 ± 1, 370) and 3 (2, 423 ± 1, 350). Young infants with PWS also had significantly (P = 0.009) higher total ghrelin levels than did the sibling controls. Nutritional phase is an important independent prognostic factor of total ghrelin levels in individuals with PWS. Circulating ghrelin levels are elevated in young children with PWS long before the onset of hyperphagia, especially during the early phase of poor appetite and feeding. Therefore, it seems unlikely that high ghrelin levels are directly responsible for the switch to the hyperphagic nutritional phases in PWS. © 2014 Wiley Periodicals, Inc.